Development of strategic action plan (SAP) risk management framework / Zaibunnisa Abdul Haiyee ... [et al.] - Abdul Haiyee, Zaibunnisa; Saipuddin, Siti Fatimah; Saad, Nor Hayati; Yahya, Mohamad Faizul (2023)
UiTM2025, a five-year strategic plan, was developed to achieve the targeted goal of becoming a globally renowned university by 2025. To achieve the mission and vision of the university, the framework of a strategic action plan (SAP) was initiated for three strategic thrusts and nine strategic themes. Planning and monitoring all nine lead directors, 24 faculties, and 13 state campuses will be difficult without proper implementation of project management. Therefore, the University Electronic Programme Management Office (UePMO) system was developed in 2021 to facilitate project monitoring. Recent input from all university stakeholders resulted in a total of 1299 SAP projects being established in the system. However, a proper risk management framework is also needed to ensure these SAP projects can be carried out efficiently. Risk Management is an enabling function that adds value to the activities of the university and increases the probability of success in achieving our strategic objectives. It is about managing uncertainty and creating an environment where surprises are minimised. This research mainly focuses on aligning SAP projects to deliver impactful strategies to support performance indicators (PI) and is also aligned to risk categories, assessment through risk level, and mitigation plans by the project owners. The determination of risk level will assist the owner of the SAP project in developing a mitigation plan according to the severity of the risk and accelerate the achievement of the UiTM 2025 Strategic Plan.